(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1856)
A description of three excavations undertaken by Mr James Farrer in 1853 on Orkney. The author discusses the excavations, the sites themselves and the finds made at these sites. Meeting notes for March 12, 1855 are appended.